PENGARUH PROMOSI KESEHATAN DENGAN MEDIA LEAFLET TERHADAP PENGETAHUAN REMAJA PUTRI TENTANG ANEMIA DI SMA TRISOKO - Dharmayanti, Ni Deni (Universitas Mohammad Husni Thamrin, 2022)
ABSTRACTBackground: Anemia among adolescent girls is a significant health concern due to the increased demand for iron during growth and menstruation. Anemia occurs when the levels of hemoglobin, hematocrit, and red blood cells in the body fall below normal thresholds. Objective: This study aims to assess the influence of anemia education utilizing leaflet media on enhancing the knowledge of female students at SMA Trisoko. Research Methodology: The research was conducted at SMA Trisoko using a quasi-experimental design with pretest and posttest assessments. The study population comprised all female students in grades XI and XII, totaling 64 students, with a sample of 28 students experiencing anemia. Data were collected before the intervention (pretest) and after the intervention (posttest). The statistical analysis employed was the dependent T-test. Results: Prior to the intervention, the students exhibited relatively low knowledge about anemia, with an average knowledge score of 7.25 and a standard deviation of 1.81. Following the intervention, the students' knowledge significantly improved to a satisfactory level, with an average score of 11.68 and a standard deviation of 2.07. The results indicate a notable impact of the leaflet-based education on enhancing the students' knowledge about anemia, with a p-value of 0.000 (p < 0.05). The research conducted in desember 2021 Conclusion and Recommendations: This study underscores the benefits of health education utilizing leaflet media in augmenting the understanding of anemia among adolescent girls. It is recommended to continue implementing this approach to further enhance comprehension and awareness of anemia among adolescents. Keywords: Anemia, Leaflet, Knowledge, Education